Implementasi Pemenuhan Hak Narapidana Penyandang Disabilitas di Lembaga Pemasyarakatan Indonesia: Analisis dan Hambatan - Ferry Andriyan; Padmono Wibowo (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research investigates the implementation of fulfilling the rights of prisoners with disabilities in Indonesian Penitentiaryas well as the inhibiting factors that influence the fulfillment of their rights. Using descriptive qualitative research methods and a normative legal approach, this research uses library sources and secondary data to analyze the current status. The research results show that prisoners with disabilities have the same rights as other prisoners, but they require special treatment to ensure accessibility, guidance and health services that suit their needs. There are several obstacles to fulfilling these rights, including lack of accessibility within prisons, lack of special facilities, and limited awareness of the rights of prisoners with disabilities. This research concludes that improvements in fulfilling the rights of prisoners with disabilities require greater efforts, including improving accessibility of facilities and infrastructure within prisons, training prison officers on the rights of prisoners with disabilities, as well as increasing awareness of this issue in society. This research provides deeper insight into this issue and provides a basis for further steps in improving the fulfillment of the rights of prisoners with disabilities in Indonesia.